Influence Of Leadership On Employees\' Job Satisfaction - Chelliah, Sathyah (2011)
This study therefore aims to understand the influence of leadership on employees\' job satisfaction in the IT industry companies in Klang Valley and Selangor. Based on the the literature review, determinants of leadership style and leadership bahavior are used to understand the relationship with employees\' job satisfaction.